Adoption Patterns of Paddle Wheel Technology in the Mina Taruna Fish Cultivation Group - Atmanegara, Irman; Murdiyanto, Eko; Senjawati, Nanik Dara (Jurnal Dinamika Sosial Ekonomi, 2025)
This study aims to examine the assessments, considerations, and adoption patterns of paddle wheel technology by the Mina Taruna Fish Farmers Group. The approach used is qualitative with data collection techniques through in-depth interviews, observation, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results show that members' assessments of paddle wheel technology covers aspects of relative advantage, suitability, complexity, ease of testing, and visibility of results. Members considered paddle wheel technology to be beneficial because it could increase stocking density, production yield, fish quality, and harvesting time efficiency, despite increased operational costs. Considerations for adoption were divided into four categories: accept permanently, accept temporarily, reject temporarily, and reject permanently. The decision to adopt is influenced by production benefits, market conditions, technical capabilities, and capital availability. Meanwhile, rejection is generally caused by limited facilities, pond conditions, and low business motivation. Overall, the results of the study show that the adoption of paddle wheel technology is determined by the interaction between perceived benefits, resource capabilities, and the socio-economic context of group members. These findings confirm that the successful implementation of technological innovations in fish farming is highly dependent on the compatibility between technical and social factors at the farmer level.